Influence of defects on photoluminescent and photocatalytic behavior of CaO/SrTiO3 heterojunctions - Coleto Junior, Ubirajara [UNESP] (2019)
CaO/SrTiO3 heterostructures were fabricated, and their photocatalytic activity for the discoloration of Rhodamine B (RhB) dye was evaluated. SrTiO3 particles were obtained via a polymer precursor method, and heterojunctions in which CaO grew on SrTiO3 crystalline particles were prepared via a sol-gel route. Characterization was performed using X-ray diffraction, transmission electron microscopy, and ultraviolet/visible/near-infrared, Raman, and photoluminescence spectroscopy. The photocatalytic activity of the heterostructures was verified by the discoloration of RhB using UV light. Defects caused by tensile strain in the interface region were verified when the calcium oxide grew on the strontium titanate, altering the defects of the material. In the heterojunctions, the defects of the monoionized and doubly ionized O (oxygen) vacancies had a greater contribution to the photocatalytic process than the defects at deep levels generated in the stress region and the direct transfer of charge between the conduction and valence bands.